Conservative surgical repair of placenta increta invading into uterine septum: case report - Omar Yousry Elshorbagy; Mahmoud Ahmed Hamdy (Journal of Medical Case Reports, 2024)
Abstract Background The prevalence of placenta accreta spectrum is on the rise, primarily as a consequence of an increasing number of Cesarean sections. Nevertheless, uterine anomalies, particularly uterine septum, pose a notable risk factor for its occurrence. While there are limited case reports documenting the association between uterine septum and placenta adherence, most of these cases have been linked to prior hysteroscopic treatment of the septum. Notably, this case represents the first-reported instance in which a uterine septum was preoperatively diagnosed in association with placenta increta adherent to it, and subsequently managed conservatively. Case presentation A 30-year-old pregnant Egyptian female patient, who had undergone two previous cesarean sections, was diagnosed with placenta increta and had an incomplete uterine septum. She was admitted to Elshatby University Hospital in December 2021. During her surgery, it was found that the placenta was adherent to right lower aspect of the septum, as well as the right anterior, lateral, and posterior uterine walls. A conservative surgical approach was scheduled and successfully performed, and 3 months later, an ultrasound examination revealed that the uterus had returned to its normal size, with no evidence of isthmocele or synechiae. The only abnormality noted was the presence of the septum. Conclusion Ultrasound plays a crucial role in diagnosing placenta accreta and identifying any additional uterine abnormalities that may guide the planning of conservative treatment. Uterine septum represents a risk factor for placental adherence, as the placenta can indeed become adherent to it. Muscle defects may become apparent following placental separation and can often be effectively managed through the use of running sutures, obviating the need for resection of the affected portion. Trial registration clinicaltrials.gov, registered on 27 April 2021, registration number: NCT04866888, https://clinicaltrials.gov/ct2/show/NCT04866888 .